Macroeconomic and Welfare Costs of U.S. Fiscal Imbalances - Gruss, Bertrand (IMF Working Papers; Working Paper, 2012)
In this paper we use a general equilibrium model with heterogeneous agents to assess the macroeconomic and welfare consequences in the United States of alternative fiscal policies over the medium-term. We find that failing to address the fiscal imbalances associated with current federal fiscal policies for a prolonged period would result in a significant crowding-out of private investment and a severe drag on growth. Compared to adopting a reform that gradually reduces federal debt to its pre-crisis level, postponing debt stabilization for two decades would entail a permanent output loss of about 17 percent and a welfare loss of almost 7 percent of lifetime consumption. Moreover, the long-run welfare gains from the adjustment would more than compensate the initial losses associated with the consolidation period.